Applicability of scoring systems predicting outcome of transarterial chemoembolization for hepatocellular carcinoma - Vogeler, Marie; Mohr, Isabelle; Pfeiffenberger, Jan; Sprengel, Simon David; Klauß, Miriam; Teufel, Andreas; Chang, De-Hua; Springfeld, Christoph; Longerich, Thomas; Merle, Uta; Mehrabi, Arianeb; Weiss, Karl Heinz; et al. (Journal of cancer research and clinical oncology, 2020)
Purpose - Several scoring systems have been proposed to predict the outcome of transarterial chemoembolization (TACE) in patients with hepatocellular carcinoma (HCC). However, the application of these scores to a bridging to transplant setting is poorly validated. Evaluation of the applicability of prognostic scores for patients undergoing TACE in palliative intention vs. bridging therapy to liver transplantation (LT) is necessary. - - Methods - Between 2008 and 2017, 148 patients with HCC received 492 completed TACE procedures (158 for bridging to transplant; 334 TACE procedures in palliative treatment intention at our center and were analyzed retrospectively. Scores (ART, CLIP, ALBI, APRI, SNACOR, HAP, STATE score, Child-Pugh, MELD, Okuda and BCLC) were calculated and evaluated for prediction of overall survival. ROC analysis was performed to assess prediction of 3-year survival and treatment discontinuation. - - Results - In patients receiving TACE in palliative intention most scores predicted OS in univariate analysis but only mSNACOR score (p = 0.006), State score (p < 0.001) and Child-Pugh score (p < 0.001) revealed statistical significance in the multivariate analysis. In the bridging to LT cohort only the BCLC score revealed statistical significance (p = 0.002). - - Conclusions - Clinical usability of suggested scoring systems for TACE might be limited depending on the individual patient cohorts and the indication. Especially in patients receiving TACE as bridging to LT none of the scores showed sufficiently applicability. In our study Child-Pugh score, STATE score and mSNACOR score showed the best performance assessing OS in patients with TACE as palliative therapy.